2017
DOI: 10.1007/s10295-017-1974-4
|View full text |Cite
|
Sign up to set email alerts
|

Combining metabolomics and network analysis to improve tacrolimus production in Streptomyces tsukubaensis using different exogenous feedings

Abstract: Tacrolimus is widely used as an immunosuppressant in the treatment of various autoimmune diseases. However, the low fermentation yield of tacrolimus has thus far restricted its industrial applications. To solve this problem, the time-series response mechanisms of the intracellular metabolism that were highly correlated with tacrolimus biosynthesis were investigated using different exogenous feeding strategies in S. tsukubaensis. The metabolomic datasets, which contained 93 metabolites, were subjected to weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…iMAT was also used to integrate transcriptome data obtained from four different time points of the cultivation profile with the GEM of S. ambofaciens in order to understand changes in overall metabolic flux distributions during mycelial growth and spiramycin production along the time . In another study, metabolome data together with the GEM simulation were useful in narrowing a list of candidate gene manipulation targets . Analysis of metabolome data covering 93 metabolites suggested that pentose phosphate pathway, shikimate pathway, and aspartate pathway need to be better streamlined for the enhanced production of tacrolimus using S. tsukubaensis .…”
Section: Recent Applications Of Gem‐based Strategies To Enhance the Amentioning
confidence: 99%
See 2 more Smart Citations
“…iMAT was also used to integrate transcriptome data obtained from four different time points of the cultivation profile with the GEM of S. ambofaciens in order to understand changes in overall metabolic flux distributions during mycelial growth and spiramycin production along the time . In another study, metabolome data together with the GEM simulation were useful in narrowing a list of candidate gene manipulation targets . Analysis of metabolome data covering 93 metabolites suggested that pentose phosphate pathway, shikimate pathway, and aspartate pathway need to be better streamlined for the enhanced production of tacrolimus using S. tsukubaensis .…”
Section: Recent Applications Of Gem‐based Strategies To Enhance the Amentioning
confidence: 99%
“…In another study, metabolome data together with the GEM simulation were useful in narrowing a list of candidate gene manipulation targets . Analysis of metabolome data covering 93 metabolites suggested that pentose phosphate pathway, shikimate pathway, and aspartate pathway need to be better streamlined for the enhanced production of tacrolimus using S. tsukubaensis . This initial information from the metabolome data was further analyzed using the S. tsukubaensis GEM in order to pinpoint individual rate‐limiting reactions in the abovementioned metabolic pathways; simultaneous overexpression of two newly identified targets, aroC and dapA from shikimate and lysine biosynthetic pathways, respectively, led to 1.64‐fold increase in the tacrolimus production in comparison with the wild‐type .…”
Section: Recent Applications Of Gem‐based Strategies To Enhance the Amentioning
confidence: 99%
See 1 more Smart Citation
“…Some noteworthy examples include the production of tacrolimus (FK506) using Streptomyces tsukubaensis, [67][68][69] ascomycin (FK520) using Streptomyces hygroscopicus var. ascomyceticus, [70][71][72] avermectin using S. avermitilis, [73] and pristinamycin I (PI) and II (PII) using Streptomyces pristinaespiralis.…”
Section: Recent Examples Of Systems Metabolic Engineering Of Streptommentioning
confidence: 99%
“…ascomyceticus, [70][71][72] avermectin using S. avermitilis, [73] and pristinamycin I (PI) and II (PII) using Streptomyces pristinaespiralis. [74,75] To solve the issue of low production yield of tacrolimus in the natural producer, Wang et al [67] first determined the intracellular response of S. tsukubaensis to exogenous feeding of four precursors known to promote the tacrolimus biosynthesis. Using a weighted correlation network analysis (WGCNA) on a dataset containing 93 different intracellular metabolites measured with gas chromatography (GC)-MS and LC-MS/MS, metabolites highly associated with the tacrolimus biosynthesis were identified.…”
Section: Recent Examples Of Systems Metabolic Engineering Of Streptommentioning
confidence: 99%